2001
DOI: 10.1590/s0036-36342001000400012
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenge: prevention of pneumococcal disease with conjugate vaccines

Abstract: Streptococcus pneumoniae is one of the leading causes of both invasive and noninvasive diseases in the pediatric population and continues to represent a significant public health burden worldwide. The increasing incidence of antibioticresistant strains of the pathogen has complicated treatment and management of the various pneumococcal disease manifestations. Thus, the best management strategy may be the prevention of pneumococcal diseases through vaccination. Although several pneumococcal conjugate vaccines h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 124 publications
0
1
0
4
Order By: Relevance
“…La vacuna polisacárida de 23 serotipos no genera una adecuada respuesta inmunogénica en menores de 2 años. Por lo anterior, después de varios ensayos clínicos 1,2 , una vacuna conjugada proteína-polisacáridos contra 7 serotipos (PCV7) fue aprobada para su uso en los EE.UU. en febrero del año 2000.…”
Section: Introductionunclassified
“…La vacuna polisacárida de 23 serotipos no genera una adecuada respuesta inmunogénica en menores de 2 años. Por lo anterior, después de varios ensayos clínicos 1,2 , una vacuna conjugada proteína-polisacáridos contra 7 serotipos (PCV7) fue aprobada para su uso en los EE.UU. en febrero del año 2000.…”
Section: Introductionunclassified
“…But recent studies have shown that serotype specific immune responses are elicited by the antibodies and that they cross react slowly [ 14 ]. As a result the importance of the presence of the capsular polysaccharide of SPn 6A in multicomponent vaccines like Pneumovax ® has been recognized [ 15 ]. The low hydrolytic stability of the phosphodiester linkages in the clinical isolates of the SPn 6A polysaccharides poses a major drawback as it leads to low bioavailability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…O pneumococo coloniza assintomaticamente a nasofaringe, sendo uma das maiores causas de infecções do trato respiratório como a pneumonia e infecções invasivas (BOGAERT; GROOT;HERMANS, 2004;BRICKS, 1994; ECHÁNIZ-AVILÉS; SOLÓRZANO-SANTOS, 2001;KADIOGLU et al, 2008;SERRANO;MELO-CRISTINO;RAMIREZ, 2006;TORTORA;FUNKE;CASE, 2005).…”
Section: Colonização E Fatores De Riscounclassified
“…Desta forma, a vacinação como política de saúde pública é a principal e mais efetiva medida na prevenção de doenças e mortes, além de contribuir com a redução de gastos em hospitalização (ECHÁNIZ-AVILÉS; SOLÓRZANO-SANTOS, 2001 Composta pelos sorotipos 1, 2, 3, 4, 5, 6B, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19A, 19F, 20, 22F, 23F e 33F, que representam de 85-90% dos sorotipos responsáveis pela doença invasiva nos EUA e pouco mais de 80% no Brasil, apresenta uma cobertura de até 90% contra pneumonia, meningite e bacteremia em adultos jovens nos EUA, onde acima de dois anos de idade, esta vacina apresenta eficácia de 56-81% na prevenção de DPI (BRICKS, 1994;BUTLER et al, 1993;FEDSON;MUSHER;ESKOLA, 1999).…”
Section: Em Países Em Que a Incidência De Infecções Por Neisseria Menunclassified
See 1 more Smart Citation